Chemotherapy-Induced Hepatotoxicity in HIV Patients - Silvia Bressan (MDPI AG, 2021)
Human immunodeficiency virus (HIV) affects more than 37 million people globally, and in 2020, more than 680,000 people died from HIV-related causes. Recently, these numbers have decrease substantially and continue to reduce thanks to the use of antiretroviral therapy (ART), thus making HIV a chronic disease state for those dependent on lifelong use of ART. However, patients with HIV have an increased risk of developing some type of cancer compared to patients without HIV. Therefore, treatment of patients who are diagnosed with both HIV and cancer represents a complicated scenario because of the risk associated with drug–drug interaction (DDIs) and related toxicity. Selection of an alternative chemotherapy or ART or temporarily discontinuation of ART constitute a strategy to manage the risk of DDIs. Temporarily withholding ART is the less desirable clinical plan but risks and benefits must be considered in each scenario. In this review we focus on the hepatotoxicity associated with a simultaneous treatment with ART and chemotherapeutic drugs and mechanisms behind. Moreover, we also discuss the effect on the liver caused by the association of immunotherapeutic drugs, which have recently been used in clinical trials and also in HIV patients.